I Love My White Shoes - Litwin, Eric; Dean, James, 1957- (New York : Harper, 2010)
As he walks down the street, Pete the cat sings about his brand new white shoes as they change from red to blue to brown to wet.
Keywords: Shoes -- Juvenile fiction; Color -- Juvenile fiction; Cats -- Juvenile fiction